Community Adaptive Capacity of Changes in The Social-Ecological System of Sub Das Amprong In The Village of GubukKlakah, Malang - Kliwon Hidayat; Mas Ayu Ambayoen; Medea Rahmadhani Utomo (IPTEK Journal of Proceedings Series, 2019)
Rural areas are currently faced a spectrum of changes that vary from changes in ecosystem conditions to their socioeconomic impacts. Each rural condition has different resilience in accordance with the respective social ecological conditions. The purpose of this research are: (1) Describing the social ecological conditions of the Amprong Sub-watershed community in GubukKlakah Village; and (2) Identifying the adaptive capacity of the community for changing socio-ecological conditions. This research uses qualitative approach. Research informants were determined by snow ball sampling and data collection was done through in-depth interviews. Data analysis was performed using the interactive model of Miles and Huberman while the validity data was carried out by triangulation of sources and methods. The results showed that the social ecological conditions of the community including suitable climate, thick top soil which is more than 50 m, and agricultural products’ quality. The vulnerability could be caused by both ecological and economic factors. Ecological factors included topographic contoured soil could cause erosion, decreasing in soil fertility, and drought. Thus, fluctuated commodity prices could also generate the vulnerability. The adaptive capacity of the community in responding to this vulnerability is demonstrated by organic fertilization, intercropping planting systems, and rejuvenation arrangements to regulate harvest time.